The Effect of Parental Social Status in Academia: Comparative Case of the Public/Private University in Morocco - Aamro, El Hassan; Chafiq, Nadia; Radid, Mohamed; Talbi, Mohammed (International Journal of Engineering Pedagogy (iJEP), 2023)
In the education system, the different parental resources of university students are linked to social inequality by distinct mechanisms, they are reproduced and legitimized. The socio-economic status (SES) of students assumed to be indexed, by the level of education, parental occupation, or family income, is a predictor of educational outcomes. The implementation of interventions that reduce the gap in the achievement of Socio-Economic Status (SES), can face significant ideological obstacles. In a purely sociological approach, our comparative study analyzes through a questionnaire survey, the socio-economic and cultural environment of the students of two Moroccan universities, the Faculty of Sciences Ben M'Sick (FSBM) of Casablanca, a public institution, and a private institution located in the same city but geographically in an upscale neighborhood. The results obtained attest that the social and cultural heritage of parents transmitted to students has effects on social reproduction, as well as the strong significant involvement of social origin in the learning process.